Transient Influence of the Reduction of Deepwater Formation on Ocean Heat Uptake and Heat Budgets in the Global Climate System. Issue 3 (8th February 2022) - Suzuki, Tatsuo; Komuro, Yoshiki; Kusahara, Kazuya; Tatebe, Hiroaki
Abstract: The formation and spreading of dense deepwater in the polar regions play a key role in one of the most important climate systems, namely ocean meridional overturning circulation, and the deepwater formation is projected to decrease under the global warming. However, the impact of the reduced deepwater formation on the climate system has not been explored in detail. Here, we performed a series of numerical experiments with a climate model where the downward water mass transport through the bottom boundary layer is artificially reduced to quantitatively evaluate its impacts on the transient ocean and climate responses. It is demonstrated that changes in deepwater formation have non‐negligible impacts on not only ocean heat content but also the Earth's radiation budget at the top of the atmosphere: reduction in deepwater formation in high‐latitude oceans causes warming of bottom water, cooling of the ocean surface, and a subsequent decrease in outgoing longwave radiation. Plain Language Summary: The sinking and spreading of cold, dense water into the ocean deep layers at high latitudes plays a crucial role in large‐scale ocean circulation, closely linked to the climate system. In this study, we use a climate model to investigate the impact of the reduced dense deepwater formation on the heat budget of the climate system, aiming at a comprehensive understanding of deepwater formation in a warming climate transition. The results show that changes in the dense water formation have a non‐negligible effect on the heat budget of the atmosphere as well as on the heat content of the ocean. A decrease in deepwater formation in the high‐latitude oceans leads to warming of the bottom waters, cooling the ocean surface, and a concomitant decrease in outgoing longwave radiation. Key Points: We evaluate the impacts of reduced deepwater formation in a climate model by adjusting the parameters of the bottom boundary layer Weakening the downward water mass transport through the bottom boundary layer leads to increased net heat transport to the deep ocean Changes in deepwater formation have non‐negligible impacts on ocean heat content and the atmospheric heat balance